The Analysis Spoken Genre Across American and Indonesian Cultures Through Podcast: Joe Rogan and Deddy Corbuzier - Kalyana, Putu Titha (Universitas Pendidikan Ganesha, 2022)
Language, of course, is a tool of communication that cannot be divorced from daily activities. Speak genre analysis has resulted in a substantial number of studies on English in many genres like as presentations, speeches, interviews, and casual chats. Podcasting is an important emerging digital media that has long been used in education. As a result, it is necessary to evaluate whether the spoken genre in each country's podcast differs. This study aims to analyze the difference between cultures in Indonesia and America, especially in podcasts entertainment and to examine whether podcasts may impact discourse genres, mainly spoken genres across cultures, and was inspired by the applications and advantages of podcasts stated above and experimentally tested by various experts. This research uses descriptive qualitative research methods. The object of this research study is a conversation between two different podcasts, namely podcasts from Deddy Corbuzier and Joe Rogan. The practical aspect is the form of questions in every conversation between the two podcasts. The data source for this research is the YouTube channel account of Deddy Corbuzier and Joe Rogan. Data collection in this study was carried out using several techniques, including observation techniques, listening techniques and note-taking/writing techniques. Result showed there was a significant different between differences in language use, different types of questions, and speaking dominance between hosts and guest stars. Thus, the difference between spoken genres across Indonesia and America can be seen.